Modeling transport of energetic particles in corotating interaction regions: A case study. Issue 1 (23rd January 2016) - Zhao, Lulu; Li, Gang; Ebert, R. W.; Dayeh, M. A.; Desai, M. I.; Mason, G. M.; Wu, Z.; Chen, Y.
Abstract: We investigate energetic particle transport in corotating interaction regions (CIRs) through a case study. The CIR event we study occurred on 8 February 2008 and was observed by both the Advanced Composition Explorer (ACE) and the twin Solar TErrestrial RElations Observatory (STEREO) B spacecraft. An in situ reverse shock was observed by STEREO B (1.0 AU) but not ACE (0.98 AU). Using STEREO B observations and assuming the CIR structure does not vary significantly in the corotating frame, we estimate the shock location at later times for both the STEREO B and ACE observations. Further assuming the accelerated particle spectral shape at the shock does not vary with shock location, we calculate the particle differential intensities as observed by ACE and STEREO B at two different times by solving the focused transport equation using a Monte Carlo simulation. We assume that particles move along Parker's field and experience no cross‐field diffusion. We find that the modulation of sub‐MeV/nucleon particles is significant. To obtain reasonable comparisons between the simulations and the observations by both ACE and STEREO B, one has to assume that the CIR shock can accelerate more particles at a larger heliocentric distance than at a smaller heliocentric distance. Key Points: New code of CIR energetic particle transport extends earlier analytical work Event fitting yields the solar wind turbulence level and the seed population Implication on particle cross‐field diffusion